STUDY ON EXTRACTION PROCESS OF TANNINS FROM SEMEN CUSCUTAE AND THEIR ANTI-PAPILLOMA ACTIVITY - Wang, Jiangning; Li, Xiaorong; Gao, Lei (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this paper was to study the extraction methods of tannin constituents from Semen Cuscutae and their anti-papilloma effects. Single factor test and orthogonal design methods were used to determine the optimal extraction method; the mouse skin papilloma model induced by DMBA/croton oil was established, which was a classic two-stage carcinogenesis model being used to observe and evaluate the anti-carcinogenic effects of tannins extracted from Semen Cuscutae in different stages. The optimal extraction method of Semen Cuscutae was a 20-fold volume of solvent, a temperature of 50 oC, three times of extraction, with 20 min each, skin papilloma experiment revealed that the number of bearing tumors gradually reduced, and the inhibition rate gradually increased with the increase of dose, in the high-dose group, its inhibition rate reached 70.2%. Tannin extract from Semen Cuscutae has an obvious inhibitory effect on skin papilloma development.